Sosialisasi Hasil Riset Perkembangan Bahasa Inggris Santri di Pesantren Berbasis Pendekatan Dynamic Usage Based (DUB) - Aziez, Feisal; Herdian, Herdian; Miftahul, Furqon; Intan, Sofiana (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2022)
This service program has two basic objectives. The first objective is to disseminate the results of ongoing research that has been carried out at partner Islamic boarding schools from 2014 to 2020 regarding the development of the English language of students. Overall, the findings of studies that have been carried out show that learners make almost all progress in the first six months and then they tend to be stable and stagnant in the forms and expressions of the English they use, which can be considered as a fossilized system that is the hallmark of pidginization. During their interactions, the non-target-like (NTL) output they produce is rarely corrected, perhaps because the learner does not know that the forms are not like the target language. It is also clear that students in pesantren have only limited exposure to input from authentic L2 or from more proficient people because the input they receive is mostly from their peers. In addition, the types of instruction they receive from their teachers are generally lexical based. These factors can cause the development of learners to stagnate. The very extensive role of peer interaction has also led to the process of pidginization or fossilization of students' English. The results of this continuous research become the basis for evaluating the English language learning program at partner pesantren which has been running for 30 years without any significant changes in program design. The second objective is to plan new English learning programs and teaching materials based on the research results.